A case study on the real time transmission system for research funds - Hoon Hong, Ji; Soo Park, Hark; Ho Kim, Dae (International Journal of Engineering and Technology, 2018)
Background/Objectives: With aview topreventing the abuse and misuse of national research and development funds, which is increasing day by day, thisstudy investigated how systems can be efficiently constructed and redundant development can be minimized when systems are linked with those of variousmanaging institutions which support research and development funds from the viewpoint of research conducting institutions that have been provided with research and development funds.Methods/Statistical Analysis: This study was conducted with aK government-funded research institute, which is a research conducting institution, in coordination with three institutions; the Ministry of Trade, Industry and Energy, the National Research Foundation of Korea, and the Institute for Information & Communications Technology Promotion.These institutions manage research & development projects.Findings: Inthis study, to prevent the abuse, misuse, and unjust execution of national research and development funds, research-fundcard companies, research managing institutions, and research conducting institutions were linked with each other in real time.First,work efficiency was improved by setting a procedure through which the conducting institutions receive card use details from card companies when research fundcards have been used to execute funds in linkage with the internal executionsystems of the conducting institutions. The data on the execution of funds are transmitted to the managing institutions in real time to enable monitoring in real time.In the past, a conducting institution had to construct a linked system and revise the internal management and execution systems every time a research project from a new managing institution was implemented.Therefore, in this study, when systems were linked, the systems were not directly linked to the DB table, but transmitted/received data by managing institution were analyzed to construct an integrated view and the integrated view was linked with conducting institutionsâ€™ internal systems to minimize redundantsystem development.Improvements/Applications: Unjust execution of research and development funds could be prevented in advance, and the transparency of research fund execution could be improved through system linked inreal time. In addition, the expandability of internal systems was improved through the system links and redundant system development when new projects are implemented could be minimized.Â Â